User Perception on Electronic Payment Services in Kathmandu Valley - Timilsina, Satyendra (NRB Economic Review, 2020)
There have been significant efforts in Nepal to increase the outreach of electronic payments services (EPS) in the last couple of years but the usage of these services has not seen significant progress. People are showing reluctance to accept the new form of payments as there are issues on users’ acceptance of this new mode. There is a need to understand users’ perception on EPS and act accordingly to improve the usage. This paper analyses users’ perception on EPS from four aspects - perceived ease of use, perceived usefulness, perceived security and perceived trust. Results of the survey show that there are low average mean scores for security and trust when compared to perceived usefulness and ease of use. Respondents have cited accessibility of EPS as one of the major issues behind such a low usage. Most of the responses are found to be independent by gender, age group, income level and other attributes. Further, perceived usefulness and ease of use have higher effect on willingness to adopt EPS in future when compared to perceived security and perceived trust.